2023
DOI: 10.1002/jgm.3623
|View full text |Cite
|
Sign up to set email alerts
|

Association between gut microbiota and seven gastrointestinal diseases: A Mendelian randomized study

Shuang Jing Zhu,
Zhen Ding

Abstract: BackgroundObservational research has shed light on the ability of gut microbes to influence the onset and progression of gastrointestinal diseases. The causal relationships between specific gut microbiomes and various gastrointestinal conditions, however, remain unknown.MethodsWe investigated the relationship between gut microbiota and seven specific gastrointestinal disorders using a robust two‐sample Mendelian randomization (MR) approach. The inverse variance‐weighted (IVW) method was used as the primary ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
4
0
1
Order By: Relevance
“…However, these findings varied from the results obtained from biobanks in the UK and Japan. [29, 30]. All this evidence suggested that the PC-related gut microbiota signatures varied across different populations.…”
Section: Discussionmentioning
confidence: 94%
“…However, these findings varied from the results obtained from biobanks in the UK and Japan. [29, 30]. All this evidence suggested that the PC-related gut microbiota signatures varied across different populations.…”
Section: Discussionmentioning
confidence: 94%
“…Our study employed the MR methods to investigate a causal relationship between GM and PC, aligning with the results of previous studies. 12 , 13 , 14 , 15 , 16 They revealed various associations between different types of GM and PC due to the differences in the data sources used. Besides validating the causal relationship between GM and PC, we utilized SMR methods to integrate GM GWAS with blood cis‐eQTLs data and blood cis‐mQTLs data, respectively, aiming to identify genes in the blood tissue affected by GM.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 Currently, MR methods have been increasingly applied to investigate the causal relationship between GM and PC. 12 , 13 , 14 , 15 , 16 However, the genes potentially involved in interactions between GM and PC remain poorly understood. To address this, Summary data‐based Mendelian Randomization (SMR) methods have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…В работе M. Signoretti и соавт. отмечается связь между активностью воспалительных процессов в ПЖ и микробным составом кишки, однако авторы делают акцент на течении хронического панкреатита, отмечая, что данные относительно связи стеатоза ПЖ и микробиома кишки освещены в литературе достаточно скудно [14].…”
Section: патогенезunclassified